2017
DOI: 10.1017/s0007114517000125
|View full text |Cite
|
Sign up to set email alerts
|

Values for digestible indispensable amino acid scores (DIAAS) for some dairy and plant proteins may better describe protein quality than values calculated using the concept for protein digestibility-corrected amino acid scores (PDCAAS)

Abstract: An experiment was conducted to compare values for digestible indispensable amino acid scores (DIAAS) for four animal proteins and four plant proteins with values calculated as recommended for protein digestibility-corrected amino acid scores (PDCAAS), but determined in pigs instead of in rats. Values for standardised total tract digestibility (STTD) of crude protein (CP) and standardised ileal digestibility (SID) of amino acids (AA) were calculated for whey protein isolate (WPI), whey protein concentrate (WPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
185
3
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(236 citation statements)
references
References 24 publications
23
185
3
7
Order By: Relevance
“…33 The other reason could be just the properties of soy proteins. Mathai et al (2017) 34 determined the standardised ileum digestibility (SID) of amino acids from whey and soy protein isolates. They confirmed that the SID of indispensable amino acids for soy amino acids was 1 to 4% lower than dairy proteins.…”
Section: Protein and Nitrogen Balancementioning
confidence: 99%
“…33 The other reason could be just the properties of soy proteins. Mathai et al (2017) 34 determined the standardised ileum digestibility (SID) of amino acids from whey and soy protein isolates. They confirmed that the SID of indispensable amino acids for soy amino acids was 1 to 4% lower than dairy proteins.…”
Section: Protein and Nitrogen Balancementioning
confidence: 99%
“…The unprocessed (and thus uneatable) yam was shown to be of (marginally) better protein quality for the first SAA and second (lysine) limiting amino acids (DIAAS > 75 for population > 3 years of age). For both groundnuts and cowpeas, the first limiting amino acid was also lysine (DIAAS 27-38), the second SAA (groundnut DIAAS 40-58; cowpea DIAAS [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The DIAAS of rice, maize, wheat and sorghum were, respectively, 42-69, 37-53, 30-43 and 18-26.…”
Section: Protein Quality Of Staple Foodsmentioning
confidence: 99%
“…Foods with high protein quality (DIAAS ≥ 100) are important to bridge the nutritional gaps created by consumption of the low-quality plant-based staple foods. Animal protein sources such as dairy products, beef, chicken and eggs were animalsource foods shown to be such excellent protein sources (DIAAS ≥ 100; Table 10) (41)(42)(43) . These foods could be of importance in bridging the gap between the lack of lysine from cereals and legumes.…”
Section: Protein Quality Of Staple Foodsmentioning
confidence: 99%
“…Digestible indispensable amino acid score (DIASS) conversely is a recommended evaluation method for protein quality of human food by the Food Agricultural Organization of the United Nations (FAO) expert consultation used to overcome the limitations of the PDCAAS system utilized since 1991. DIAAS is a preferred adopted evaluation method due to some identifiable number of problems or shortcomings associated with PDCAAS values including; (a) the calculation of inaccurate values using PDCAAS procedure sometimes and (b) protein digestibility inability to reflect the digestibility of individual dietary indispensable amino acids always [43,48]. Also, the pig is considered a preferably better model to the rat in determining the ileal digestibility of amino acid in food protein in the absence of human data [43,49].…”
Section: Synopsis Of Protein Digestibility Corrected Amino Acid Scorementioning
confidence: 99%
“…According to FAO [44], protein requirements are defined in terms of consumption needed to meet metabolic requirements for maintenance as indicated by nitrogen stability in the corresponding age group including those associated with the protein needs for normal growth of infants and children, pregnancy and lactation in women. Therefore, digestible indispensable amino acid score (DIASS) values are calculated by multiplying each indispensable amino acid digestibility by the protein amino acid concentration and comparing the values to a scoring pattern [43,48,49].…”
Section: Synopsis Of Protein Digestibility Corrected Amino Acid Scorementioning
confidence: 99%